Birth Patterns and Delayed Breastfeeding Initiation in Indonesia - Tika Dwi Tama; Erni Astutik; Septa Katmawanti; Jauhari Oka Reuwpassa (Korean Society for Preventive Medicine, 2020)
Objectives This study was conducted to examine the association between birth patterns (defined in terms of birth order and interval) with delayed breastfeeding initiation in Indonesia. Methods A cross-sectional study was carried out using data from the Indonesian Demographic and Health Survey 2017. The weighted number of respondents was 5693 women aged 15-49 years whose youngest living child was less than 2 years old. Multivariable logistic regression was conducted to evaluate associations between birth patterns and delayed breastfeeding initiation after adjusting for other covariates. Results This study found that 40.2% of newborns in Indonesia did not receive timely breastfeeding initiation. Birth patterns were significantly associated with delayed breastfeeding initiation. Firstborn children had 77% higher odds of experiencing delayed breastfeeding initiation (adjusted odds ratio, 1.77; 95% confidence interval, 1.02 to 3.04; p<0.05) than children with a birth order of 4 or higher and a birth interval ≤ 2 years after adjusting for other variables. Conclusions Firstborn children had higher odds of experiencing delayed breastfeeding initiation. Steps to provide a robust support system for mothers, especially first-time mothers, such as sufficient access to breastfeeding information, support from family and healthcare providers, and national policy enforcement, will be effective strategies to ensure better practices regarding breastfeeding initiation.